Aspectos polêmicos da ação rescisória - Oliveira, Rodrigo Martiniano de (2011)
The motion to vacate a judgment, although foreseen for a long time in Brazilian Law, still generates great controversy both in doctrine and courts. Some of these issues will be discussed herein with the most diverse Thesis and theories about the issues in vogue. It’s not about to exhaust subject, but to bring some questions, wich has great relevance to law professionals, to a debate